Peran Rekognisi Pesantren Terhadap Fungsi Pemberdayaan Masyarakat di Era Revolusi Industri 4.0 - Saptaputra, Idil; Muzaqqi, Muhammad Kiki; Ibadin, Hasan; Lessy, Zulkipli (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2022)
This research aims to determine the role of Islamic boarding school recognition on the function of community empowerment in the era of industrial revolution 4.0. Qualitative research method, type of literature study. Data comes from books, journals, laws, government regulations, and other scientific articles. The results obtained are the challenge of Islamic boarding schools in the era of industrial revolution 4.0 is to improve the quality and development of human resources. The function of community empowerment in Islamic boarding schools is to improve the welfare of the Islamic boarding school and the community through human resources development activities, such as training and fieldwork practices, increasing economic strength and potential, implementing social activities, utilizing technology, and other activities according to the capacity of the Islamic boarding school. The role of Islamic boarding school recognition in the implementation of the empowerment function in the era of the industrial revolution 4.0, which is to become the legal basis for the implementation of the overall community empowerment function, as well as providing assistance, both facilities and infrastructure, finance, technology, and skills training.Â Keywords: Islamic Boarding School Recognition; Community Empowerment; Industrial Revolution 4.0.